EDUKASI MENGENAI COVID-19 DI RW 03 KELURAHAN BARUSARI KECAMATAN SEMARANG SELATAN KOTA SEMARANG - Lutfiyah Rizqulloh; Muhammad Iqbal (Politeknik Negeri Sriwijaya, 2023)
The case of covid-19 that occurred in Indonesia spread widely throughout the community, WHO has declared covid-19 as a world pandemic. The government continues to urge all components of society to work together in dealing with COVID-19. This service activity is carried out to educate the community, especially at the level of the community unit, by conducting socialization and distributing questionnaires to 30 residents who are in RW 03 Barusari Village. The purpose of community activities is to increase community participation in overcoming COVID-19 and see the level of community understanding. The results of distributing questionnaires on community service found that aspects of knowledge, perceptions, attitudes, community readiness, family support, support from community leaders, and good community behavior. So seeing this condition, it is hoped that the residents of RT 03 can help the government in preventing the spread of COVID-19. Keywords: covid-19, attitude, behavior, family support, community support.